Performance characteristics of five SARS-CoV-2 serological assays: Clinical utility in health-care workers. (September 2021) - Heffernan, Emma; Kennedy, Lisa; Hannan, Margaret M; Ramlaul, Navneet; Denieffe, Stephanie; Courtney, Garry; Watt, Alison; Hurley, John; Lynch, Maureen; Fitzgibbon, Maria
Study objective: SARS-CoV-2, which causes coronavirus disease (COVID-19), continues to cause significant morbidity and mortality. The diagnosis of acute infection relies on reverse transcription-polymerase chain reaction (RT-PCR)-based viral detection. The objective of this study was to evaluate the optimal serological testing strategy for anti-SARS-CoV-2 antibodies which provides an important indicator of prior infection and potential short-term immunity. Methods: The sensitivity and specificity of four different ELISA assays (Euroimmun IgG, Euroimmun NCP-IgG, Fortress and DIAsource) and one CLIA assay (Roche ELECSYS) were evaluated in 423 samples; 137 patients with confirmed RT-PCR COVID-19 infection (true positives), and 100 pre-pandemic samples collected prior to October 2019 (true negatives). A further 186 samples were collected from health-care staff and analysed by all five assays. Results: The Fortress ELISA assay demonstrated the highest sensitivity and specificity followed by the Roche ECLIA assay. The highest overall sensitivity came from the assays that measured total antibody (IgM–IgG combined) and the three assays that performed the best (Fortress, Roche, Euroimmun IgG) all have different antigens as their target proteins which suggests that antigen target does not affect assay performance. In mildly symptomatic participants with either a negative RT-PCR or no RT-PCR performed, 16.76% had detectable antibodies suggesting previous infection. Conclusions: We recommend a combined testing strategy utilizing assays with different antigenic targets using the fully automated Roche ECLIA assay and confirming discordant samples with the Fortress Total Antibody ELISA assay. This study provides an important indicator of prior infection in symptomatic and asymptomatic individuals.